(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2006)
The Mekong Regional Health Support Project's objective is to improve health services in the Mekong region and to enhance access to and coverage of these services, especially for the poor. The project consists of five components. A) Protecting the poor and near-poor - support government efforts to ensure access to health care services for poor and near-poor households. B) Curative care quality and capacity - improve the quality and capacity of hospital services in the Mekong region. C) Preventive health - build the capacity of the region's preventive health system to address long-standing and emerging infectious disease threats as well as new health challenges. D) Human resources development - improve the capacity of the health workforce to deliver quality health services, especially for the poor and near-poor. E) Project management, monitoring and evaluation - the establishment and operation of the Central Project Management Unit (CPMU), Local Project Management Units (LPMUs), and Regional Advisory Committee (RAC).
Keywords: Flood protection,Ngăn ngừa lũ lụt,Sanitation,Vệ sinh môi truờng